Pengembangan Bahan Ajar English for Islamic Education melalui Analysis, Design, Development, Implementation and Evauation (ADDIE) untuk Menunjang Pemahaman Reading dan Grammar Bagi Mahasiswa di Institut Agama Islam Bakti Negara (IBN) Tegal - Kaptiningrum, Pindha (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2024)
Learning outcomes between English lecturers vary. This happened because there was neither English book authorized by Quality Assurance Institute nor made by an English Lecturer at the Faculty of Teacher Training and Education, Institut Agama Islam Bakti Negara (IBN) Tegal. There needs to have an English book that could be used by English lecturers together. The product of the research was English for Islamic Education (EIE) books for the Faculty of Teacher Training and Education with Analysis, Design, Development, Implementation and Evaluation (ADDIE) Method. The results of the evaluation showed that English for Islamic Education book was effective and it could be used for students and lecturers.